Smart-driven and Locally Reconstructed: The Construction and Practice of a New Moral Education Mechanism for " Red Study Programs" in County-level Primary and Secondary Schools —— A Case Study of "Forestry Plus" Education in Tangwang County, Yichun City - Yong Sun (Education Research on Study Tours and Practice, 2026)
Addressing practical challenges such as fragmented moral education resources, disjointed curriculum implementation, and the weakening of students’ local identity amidst the outflow of the forest region’s population, this study is grounded in the dual regional context of "forestry transformation" and "Anti-Japanese United Army history" in Tangwang County, Yichun City. It constructs a new mechanism for "Red Study" moral education characterized by "Digital Intelligence-Driven and Local Reconstruction." Following the logical framework of "Technology Empowerment — Resource Transformation — Mechanism Guarantee," the study innovatively designs a county-level "1356" digital intelligence-driven practical model for moral education in study tours. By establishing a standardized "Three Lists" management mechanism, the study resolves the difficulties in resource coordination. Through the development of "Forestry + Discipline" interdisciplinary integrated curricula, it achieves the educational transformation of "Red and Green" resources. Furthermore, by guiding students to utilize AI modeling and AR technology to participate in the construction of "Digital Red Veins" resources, scattered red heritage sites are transformed into interactive and inheritable digital assets. Practice has demonstrated that this model effectively revitalizes dormant local red resources. It not only reshapes the local cultural identity of students in the forest region but also provides a replicable and scalable "Forest Region Sample" and "Tangwang Solution" for county-level primary and secondary schools to explore a new paradigm of moral education that "retains both people and hearts" in the age of artificial intelligence.